A Causal Association Study Between Chronic Kidney Disease and Oral Health: A Mendelian Randomization Study - Guilian Zhang; Duojiao Xu; Guoxia Yu (Health Science Reports)
ABSTRACT Background and Aims Previous studies have shown that chronic kidney disease (CKD) can lead to changes in oral health, but the conclusions remain controversial. Thus, we conducted a Mendelian randomization (MR) study from the perspective of genetic analysis to assess the causal association between CKD and oral health conditions, including dental caries, pulp diseases, periapical tissues, and diseases of the gum and periodontal tissues. Methods We performed inverse variance weighted (IVW) random effects MR analyses and several sensitivity MR analyses using summary statistics from genome‐wide association studies (GWAS). The data were derived from the European population in 2021, which included 3902 cases of CKD, 4170 cases of dental caries, 5354 cases of diseases of the pulp and periapical tissues, and 4120 cases of gingivitis and periodontal diseases. Results We found a positive causal relationship between CKD and dental caries, and the effect odds ratio (OR) of CKD on dental caries was 1.368 (95% CI, 1.124–1.664; p = 0.002). There was no direct causal relationship between CKD and diseases of the pulp and periapical tissues and diseases of the gum and periodontal tissues, with the effect OR of 1.176 (95% CI, 0.973–1.420; p = 0.094) and 1.201 (95% CI, 0.977–1.477; p = 0.08). Conclusions Our findings suggest that CKD could affect oral health and only with a direct causal link to dental caries. However, pulp diseases, periapical tissues, and diseases of the gum and periodontal tissues have no direct causal relationship.